Menghidupkan Storynomic Tourism: Mempromosikan Kuliner Ponorogo Melalui Penulisan Feature - Hanidar, Sharifah; Moehkardi, Rio Rini Diah; Hernawati, Mala; Zahroh, Adiba Qonita (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
By taking into account the COVID-19 pandemic situation, which has a very significant impact on the education, economy, and tourism sectors, the Community Service Team of the English Studies Program, Faculty of Cultural Sciences, Universitas Gadjah Mada designed a series of training programs on feature writing focusing on the theme of Ponorogo unique culinary. The series of activities carried out in a blended learning method (online and offline) were intended for Class X students of SMAN I Babadan, Ponorogo, East Java. The activities were designed to improve the students’ writing and soft-skills, and to promote Ponorogo culinary tourism by applying a narrative-based tourism approach or creative content, which is also known as storynomic tourism. The team facilitated a series of training sessions on writing popular articles, assisted the students in conducting direct observations and interviews with the local culinary entrepreneurs, and assisted them in writing interesting features in either Indonesian or English. The output of the activity is a book entitled “Kumpulan Ulasan Kuliner Khas Ponorogo, Jawa Timur” published by the English Studies Program, Faculty of Cultural Sciences, Universitas Gadjah Mada. ==== Dengan memperhatikan situasi pandemi COVID-19 yang berdampak sangat signifikan pada sektor pendidikan, ekonomi, dan pariwisata, Tim Pengabdian kepada Masyarakat (PkM) Prodi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Gadjah Mada merancang sebuah program pelatihan dan pendampingan penulisan feature yang mengangkat tema kuliner khas Ponorogo. Rangkaian kegiatan yang dilakukan secara bauran (daring dan luring) ini ditujukan untuk siswa- siswa Kelas X SMAN I Babadan, Ponorogo, Jawa Timur. Kegiatan ini bertujuan meningkatkan keterampilan menulis dan softskills para siswa serta mempromosikan wisata kuliner Ponorogo dengan menerapkan pendekatan pariwisata yang berbasis narasi atau konten kreatif yang dewasa ini juga dikenal dengan storynomic tourism. Tim PkM memfasilitasi pelatihan penulisan artikel populer, mendampingi siswa-siswa melakukan observasi dan wawancara langsung kepada para pelaku usaha kuliner lokal Ponorogo, serta mendampingi proses penulisan feature yang menarik dalam bahasa Indonesia atau Inggris. Luaran dari kegiatan PkM ini adalah sebuah buku berjudul “Kumpulan Ulasan Kuliner Khas Ponorogo, Jawa Timur” yang diterbitkan oleh Prodi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Gadjah Mada.